Uji Efektifitas Ekstrak Tanaman Sebagai Nematisida Nabati untuk Menekan Populasi Nematoda Puru Akar (Meloidogyne spp.) pada Tanaman Seledri (Apium graveolens L.) - Shaffila, Diaz Mutiara; Singarsa, I Dewa Putu; Sudarma, I Made (Agrotrop : Journal on Agriculture Science, 2023)
Testing the Effectiviness of Plant Extracts as Botanical Nematicides to Suppress the Population of Root Knot Nematodes ( Meloidogyne spp.) on Celery Plants ( Apium graveolens L.). Root knot nematodes ( Meloidogyne spp.) are one of nematodes that attack various types of important agricultural crops. This nematode is found on plant roots and can cause symptoms such as stunting, root knot, and wilting in plants. One effort to control nematodes is to use botanical nematicides. Based on this, research will be carried out to suppress the population of root knot nematodes ( Meloidogyne spp.) using plant leaf extracts of Marigold ( Tagetes spp.), soursop ( Annona muricata L.), papaya ( Carica papaya L.), neem ( Azadirachta indica ), and jatropha plant ( Jatropha curcas L.). The research methods are: (1) Making plant leaf extracts, (2) Making solution of Meloidogyne spp., (3) Testing the ability of several plant leaf extracts in pots/polybag. The purpose of this study was to determine the plant leaf extracts were able to suppress the population of Meloidogyne spp. The results showed that the nematode population/300 g soil, Tagetes spp. extracts was the best in suppressed the population, 22,2 mesh (75,3%), Jatropha curcas L. 25,4 mesh (71,7%), Carica papaya L. 28,0 mesh (68,8%), Azadirachta indica 31,6 mesh (64,8%), dan Annona muricata L. 34,0 mesh (62,2%). In calculating the nematodes population/1 g of root, it is Tagetes spp. the best extract suppressed the population of root knot nematode, namely 21,2 mesh (69,5%), Jatropha curcas L. 24,0 mesh (65,5%), Carica papaya L 27,4 mesh (60,6%), Azadirachta indica 30,8 mesh (55,7%), dan Annona muricata L. 33,4 mesh (52,0%).